A Literature Review on Handwritten Character Recognition based on Artificial Neural Network - Singh, Rajdeep; Mishra, Rahul Kumar; Bedi, S.S; Kumar, Sunil; Shukla, Arvind Kumar (International Journal of Computer Sciences and Engineering, 2025)
In current scenario, character recognition is the most important field of pattern recognition because of its application in numerous fields. Optical Character Recognition (OCR) and Handwritten Character Recognition (HCR) has specific domain to use. OCR system is most fitted for the applications like multi selection examinations, written communication address resolution etc. In returning days, character recognition system would possibly function a key issue to make paperless setting by digitizing and process existing paper documents. During this paper, we have planned the detail study on existing strategies for hand written character recognition based on ANN. This paper presents an in depth review within the field of handwritten Character Recognition